2001
DOI: 10.1046/j.1365-4362.2001.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus vulgaris: environmental factors. Occupational, behavioral, medical, and qualitative food frequency questionnaire

Abstract: The beneficial effect of smoking on pemphigus might be explained by its effect on the immune system. In addition, smoking has an antiestrogenic effect, while pesticides have an estrogenic effect. The lower numbers of smokers among patients, the higher exposure rates to pesticides, and the higher number of female patients who had been pregnant may point to the contribution of estrogens to the disease process. It remains to be determined whether measures, such as avoiding exposure to pesticides or metal vapor, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
4
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 49 publications
9
124
4
11
Order By: Relevance
“…These findings suggested that this may point to the contribution of estrogens in the disease process (Brenner et al, 2001).…”
Section: Other Factorsmentioning
confidence: 84%
“…These findings suggested that this may point to the contribution of estrogens in the disease process (Brenner et al, 2001).…”
Section: Other Factorsmentioning
confidence: 84%
“…Bu verilerin aksine Valikhani ve Bastuni araştırmalarında gebelik sayısında bir artış saptamamış, ancak pemfiguslu hastalarda oral kontraseptif kullanımı-nın daha sık olduğunu bildirmişlerdir. 6,10,11 Bizim hastalarımızın çok sayı-da gebelik geçirmiş olmaları çoğunun Doğu ve Güneydoğu Anadolu bölgelerinden geliyor olmalarına ve o bölgelerde Türkiye geneline göre gebelik oranı ve doğum hızının yüksek olmasına bağlı olabilir. 12 Pemfigusun bazı otoimmün hastalıklarda olduğu gibi infertilite ile ilişki-si olduğu da ileri sürülmüştür.…”
Section: Discussionunclassified
“…Several studies on the effect of smoking on pemphigus seem to suggest that, at least in some populations, it has a protective effect. 3 A rare endemic form of pemphigus foliaceus (fogo selvagem) has been identified in parts of Brazil and in North Africa. 4 The cause remains to be identified, but cases seem to cluster in rural villages around rivers and resolve when patients move away from the endemic areas.…”
Section: Epidemiologymentioning
confidence: 99%
“…Paget's disease is an intra-epidermal carcinoma seen in the nipple and areola area (mammary Paget's) or anogenital and axillary skin (extramammary Paget's). 3 Paget's disease of the breast presents as unilateral, sharply demarcated nipple eczema or erosion, often with bleeding or nipple discharge, in association with underlying intraductal adenocarcinoma of the breast or non-invasive carcinoma. Extramammary Paget's disease is characterised by an itchy, moist, well-defined erythematous plaque, typically in the anogenital area and most common in elderly women.…”
mentioning
confidence: 99%